The Relationship Between Creative Thinking Skills and Learning Outcomes of Grade III Elementary School Students - Septiyana, Septiyana; Ifrianti, Syofnidah; Negara, Hasan Sastra (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the relationship between creative thinking skills and the learning outcomes of third-grade elementary school students in the Indonesian language subject. The method used in this study is a quantitative approach with a correlational research type. The population in this study consists of all third-grade students, totaling 25 participants. The data collection tool used is a test to find data on creative thinking skills in relation to learning outcomes. The prerequisite tests used are normality tests and linearity tests. The data analysis technique in this study uses Pearson correlation test (product moment correlation). The analysis results show that there is a significant relationship between the creative thinking skills of students and the learning outcomes of third-grade students in the Indonesian language subject.